Effects of time of day on race splits, kinematics, and blood lactate during a 50-m front crawl performance - Lisbôa, F. D.; Raimundo, J. A.; Pereira, G. S.; Ribeiro, G.; de Aguiar, R. A.; Caputo, F. (The Journal of Strength and Conditioning Research, 2021)
This study aimed to investigate the performance, race splits, metabolic, and stroke parameters during 2 successive 50-m front crawl under conditions simulating a competition. Eleven competitive male swimmers (20 ± 3 years, 182 ± 5 cm, and 77 ± 5 kg) performed 2 successive 50-m front crawl trials in a 50-m swimming pool at 10 am and 5 pm. Block time (tB), 15-m performance (t.15-m), and 50-m performance (t.50-m) were measured. Velocity (V), stroke rate (SR), stroke length (SL), and stroke index (SI) were measured at 3 time points during the trials. Pre-trial and post-trial blood samples were taken to determine blood lactate accumulation (delta[Lac]). For t.50-m, the relative difference between 10 am and 5 pm reached 0.1% (p = 0.7; effect size [ES] = 0.02). Furthermore, no differences in tB (p = 0.12; ES = -0.28) and t.15-m (p = 0.39; ES = -0.16) were observed between periods. Both V (p = 0.11; ES = -0.14) and SI (p = 0.16; ES = 0.15) were also similar. Higher values of SR were recorded at 10 am (p = 0.03; ES = -0.32), whereas the morning values of SL were lower (p = 0.04; ES = 0.3). delta[Lac] was not significantly different between periods (p = 0.07; ES = -0.27). Although time of the day did not impact performance in 2 successive 50-m front crawl performances, different stroke parameters profiles were observed during these trials. This may help coaches design specific warm-up exercises to enhance performance at different times of the day.